Blast injury of the finger caused by mobile battery explosion: A case report - Suguru Hagiwara (Elsevier, 2021)
Lithium-ion batteries can cause several types of injuries upon explosion due to misfire. We report a case in which a mobile battery explosion resulted in high-pressure injection of metal debris into a small entry point on the skin creating puncture wounds on a patient's index finger, necessitating surgical intervention for massive debridement. A healthy 45-year-old, right-hand-dominant woman presented to the emergency department 4 h after a mobile battery had exploded in her left hand, causing burns to the left index finger. The battery had exploded due to misfire because the patient had accidentally hit it with a hammer. Radiographs of the index finger demonstrated foreign material extending from the fingertip to the ulnar proximal phalanx along the flexor tendon sheath, which was consistent with a high-pressure injection injury. She underwent semiurgent incision, irrigation, and debridement of the left index finger the day after the injury. The wound healed uneventfully within a month. At the 6-month follow-up, the palm-to-tip distance was 1 cm, and sensation at the tip was recovered. Compositional analysis of the debris revealed that the two major elements were aluminum and nickel (both less than 10%); lithium constituted less than 1% of the debris, a level deemed safe in humans. The protocol of semiurgent incision, irrigation, and debridement was safe and effective in the treatment of the injection injury caused by the mobile battery explosion.